Walking the road together? EU polity maintenance during the COVID-19 crisis. Issue 5 (19th September 2021) - Ferrera, Maurizio; Miró, Joan; Ronchi, Stefano
Abstract: This article investigates the 'conflict parabola' of the negotiations between EU member states during the COVID-19 pandemic. The crisis reopened the foundational controversy over cross-national solidarity under economic adversities. After a peak of conflict in March–April 2020, the political climate gradually shifted from antagonism to appeasement, creating the conditions necessary for the adoption of the Next Generation EU plan. Building on the negative experiences of past crises, some EU leaders engaged in a strategy of 'polity maintenance', i.e. keeping the EU polity together, regardless of interest-based divisions. This strategy mainly rested on public communication. The article documents both conflict and appeasement by analysing a corpus of leaders' quotes drawn from the press (covering eight countries) and a corpus of speeches by Angela Merkel. The Chancellor made a high political investment in EU polity maintenance, presenting European cohesion as part and parcel of Germany's national interest.